Analisis Fatwa MUI Tentang Tes Swab Untuk Mendeteksi Covid-19 Saat Berpuasa Perspektif Pandangan Ulama dan Relevansinya - Yola Zulyenni (Institut Agama Islam Negeri Palopo, 2023)
Circular Letter of the Covid-19 Handling Task Force Number 11 of 2022 concerning Provisions for the Travel of Domestic Persons During the Covid-19 Pandemic Period is the basis for revoking the obligation for Rapid antigen tests for people who have received full doses of vaccines and booster vaccines, but are required to comply with health protocols. People who receive the first dose of the vaccine and who have not received the vaccine for reasons of special health conditions must show negative results from the RT-PCR test or rapid antigen test. This regulation also applies to travellers who are fasting. One prohibition that must be avoided while fasting is putting something into the body. In response, the Indonesian Ulama Council issued fatwa number 23 of 2021 concerning the Swab Test to Detect Covid-19 While Fasting, which states that the swab test does not break fast. So it is necessary to study how the views of the Ulama on this fatwa and its relevance to the situation when this fatwa was decided. This study uses the method of literature review. The approach used is the ushul fiqh approach, and the theory used is istihsan. The primary legal material used is the MUI Fatwa Number 23 of 2021, and the secondary legal material used is books and journal articles. The purpose of this study was to find out the views of the Ulama on the results of the MUI's Ijtihad in establishing Fatwa Number 23 of 2021 so that there is no doubt when carrying out a swab test while fasting and whether this MUI fatwa is relevant to the situation at the time this fatwa was decided. The study's results show that Ulama's views on the results of the MUI's Ijtihad in establishing Fatwa Number 23 of 2021 are divided into two opinions. Most contemporary scholars say that the law on swab testing during fasting does not break the fast. According to the classical ulama, the Hambali and Shafi'i ulama declared it null and void. The Maliki school of thought believes there is a gap for the swab not to break the fast because it is a dry and solid object that does not reach the stomach. The Hanafi school believes that the swab is not invalidated because it does not enter the body perfectly. MUI's decision-making in establishing Fatwa No. 23 of 2021 is considered relevant to the situation when this fatwa was issued. This fatwa is an effort to emphasize the spread of Covid-19.